EVALUATION DE L’ACTIVITÉ ANTIFONGIQUE DE FICUS PLATYPHYLLA DEL. (MORACEAE) - Apeti, Gbogbo Koffi; Marra, Dourma; Semihinva, Akpavi; Komlan, Batawila; Koffi, Akpagana (European Scientific Journal, ESJ, 2013)
To validate the traditional use of plants in the treatment of certain fungal infections due to AIDS, Ficus platyphylla (Moraceae), a plant used in traditional medicine in Togo in the treatment of the opportunist diseases of the AIDS has been investigated for its antifungal properties. Aqueous and hydro- ethanolic stem bark extracts were tested on nine fungal strains including six yeast (Candida krusei, C. zeylanoides, C. albicans, Cryptoccocus neoformans, Geotrichum candidum and Rhodotorula rubra) and three filamentous (Aspergillus fumigatus, Microsporum gypseum and Trichophyton mentagrophytes) by the method of broth dilution. The results show that the extracts are active against dermatophytes, Cr. neoformans and Candida species except C. krusei with MICs ranging from 0.25 to 2 mg.ml-1. The hydro- ethanolic extract presented a fungicidal activity on all strains inhibited. The presence of tannins, saponins and sometimes alkaloids, would be the possible cause of the antifungal activities observed. These results justify the traditional use of this plant as an antifungal.